Approximation methods for distributions of aggregate insurance losses - Karpickaitė, Valerija (Lietuvos matematikos rinkinys, 2025)
The distribution of aggregate claims of a portfolio has been a central topic in risk theory. The discussion has focussed on two problems: the choice of the distribution and its numerical evalution by means of an approximation. The paper describes the method of approximation by means of orthogonal polynomoales, the Edgeworth and the Esscher methods.